ANALISIS PENGARUH PENILAIAN KINERJA, REWARD, DAN PUNISHMENT TERHADAP KINERJA PEGAWAI PADA CV. SAPROTAN UTAMA DEMAK - Ghanitri, Elyana (Program Studi Manajemen Fakultas Ekonomi UST, 2024)
The quality of a company's human resources is a key factor in the overall success of a business. Organizations can enhance productivity by investing in their human resources and considering performance evaluation, rewards, punishments, and job satisfaction. The objective of this study is to analyze the influence of performance evaluation, rewards, and punishments on employee performance at CV. Saprotan Utama. The population in this study consists of all employees of CV. Saprotan Utama in Demak. The sampling technique used in this research is probability sampling (Simple Random Sampling). The data analysis results indicate that the questionnaire instrument is valid and reliable, and there are no violations in the classical assumption tests. The multiple linear regression analysis results indicate that the coefficient of the Punishment variable is the highest, thus making it the most dominant variable in influencing employee performance. The F-test results show that performance evaluation, rewards, and punishments collectively influence employee performance at CV. Saprotan Utama. Meanwhile, the t-test results indicate that performance evaluation and punishments significantly affect employee performance, whereas the reward variable does not have a significant impact.